The value of revascularization and adherence to therapy in the development of cardiovascular complications in long-term monitoring of patients with myocardial infarction of the right ventricle on the background of the Q-myocardial infarction of the left ventricular posterior wall - V.Y. Tseluyko; T.A. Lozova; V.P. Zheleznyy; O.S. Sasyuk (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the role of deferred revascularization and adherence to drug therapy as factors affecting long-term prognosis of patients with myocardial infarction (MI) of the right ventricle (RV) on the background of the Q-myocardial infarction of the left ventricle (LV) posterior wall (PW). Materials and methods. The study involved 155 patients with MI of the RV due the Q-MI of the PWLV, age 64.11 ± 0.78 years. The revascularization (PCI, CABG) was performed within one year after MI. Adherence to treatment was assessed after 6 and 30 months. The combined endpoints included: unstable angina (UA), Re-MI, stroke and cardio-vascular (CV) death. Follow-up was 30.6 ± 4.5 month. Results. The 1st group included 68 (43.9 %) patients who underwent surgical treatment, 87 (56.1 %) patients under conservative strategy composed the 2nd group. The frequency of combined CV-point was significantly lower in the 1st group (ð = 0.00001). Revascularization after RV MI was accompanied by significant decrease of frequency of Re-MI (ð = 0.05), stroke (ð = 0.0413) and UA (ð = 0.00001) during 30 months follow-up. Reducing risk of CV events in the 1st group was associated with higher adherence to ACE inhibitors / ARA (86.7–79.4 %), statins (97.1–64.7 %) and clopidogrel (98.5–79.4 %) at 6 months and at the end of the observation period, compared to patients with conservative strategy (p < 0.05). Conclusions. Higher adherence to drug therapy in the surgical treatment group is associated with significantly lower number of cardiovascular events during 30 days after right ventricular myocardial infarction.